Diversity and distribution of medicinal plants in the Universitas Sumatera Utara Arboretum of Deli Serdang, North Sumatra, Indonesia - RAHMAWATY RAHMAWATY; J.B. SAMOSIR; R. BATUBARA; A. RAUF (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rahmawaty, Samosir JB, Batubara R, Rauf A. 2019. Diversity and distribution of medicinal plants in the Universitas Sumatera Utara Arboretum of Deli Serdang, North Sumatra, Indonesia. Biodiversitas 20: 1457-1465. The plants found in Universitas Sumatera Utara (USU) Arboretum has the potential to be utilized by the local community to meet their food and medicinal needs. The objectives of this study were to calculate the species diversity, to find out the various parts of plants utilized for medicinal purposes and to map the distribution of medicinal plants in the arboretum. Survey and interview methods were used to collect data. The species diversity was determined using Shannon-Wiener index. Geographic Information System (GIS) was used to map the distribution of medicinal plants. The results showed that there were 17 species of medicinal herbs, 21 species of trees and 12 species of poles in the arboretum. The diversity was classified as moderate based on the calculated value. The most predominant part of plants utilized for medicinal purposes were leaves. The distribution of medicinal plants was mostly clustered and uneven. The condition indicates still there is scope for additional planting of medicinal species to increase the diversity of species, especially in the western and the northern part of the arboretum.